2020
DOI: 10.1111/een.12917
|View full text |Cite
|
Sign up to set email alerts
|

Ants climb plants because they cannot swim: ant presence on flowers during the flood season reduces the frequency of floral visitors

Abstract: 1. Seasonal changes in environments may not only affect habitat connectivity but may also affect its use by species and their interactions. Thus, during the flood season, ants are forced to develop survival strategies such as vertical plant migration. 2. According to this, it has been hypothesized that the presence of ants may directly affect plant-pollinator interactions. 3. Thus, we asked the following questions: (i) Are floral visitors of Hyptis brevipes expelled due to ant presence on inflorescences during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
(67 reference statements)
0
5
0
1
Order By: Relevance
“…Moreover, pollinators can consume flower whorls of aquatic plants, simultaneously acting as florivores (e.g., Trigona spinipes in Nymphaea pulchella flowers; Chalegre et al, 2020). Previous studies have also shown that some ant species visit plants during the rainy season in the Pantanal, repelling nectar thieves and pollinators from flowers (e.g., Hyptis brevipes, see Souza et al, 2020). Ant-plant mutualistic interactions, in which ants act as biotic defenses against herbivores and florivores, are widespread across tropical plants (Heil and Mckey, 2003;Rosumek et al, 2009;Mesquita-Neto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, pollinators can consume flower whorls of aquatic plants, simultaneously acting as florivores (e.g., Trigona spinipes in Nymphaea pulchella flowers; Chalegre et al, 2020). Previous studies have also shown that some ant species visit plants during the rainy season in the Pantanal, repelling nectar thieves and pollinators from flowers (e.g., Hyptis brevipes, see Souza et al, 2020). Ant-plant mutualistic interactions, in which ants act as biotic defenses against herbivores and florivores, are widespread across tropical plants (Heil and Mckey, 2003;Rosumek et al, 2009;Mesquita-Neto et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the climatic seasonality and subsequent flooding cycle might lead to variable flower sizes throughout the year (plants during the wet season have larger flowers than plants flowering in the dry season; C. Aoki and A. L. Teixido, personal observations). Moreover, interactions between some species and ants may increase during the flood season, which may restrict pollinator visits (Souza et al, 2020) and/or change interactions with leaf and flower herbivores mediated by biotic defenses (e.g., Rosumek et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ants only “patrol” on branches, and their role in interacting with C. marginatum plants needs to be investigated. The presence and abundance of ants among the flowers may influence the behavior and frequency of visits by other floral visitors, including potential pollinators (Souza, Baronio, Weirich, Oliveira, Ferreira, Arruda, & Aoki, 2020). So, although it was not demonstrated that ants were interfering in C. marginatum pollination (this study), the information recorded here is important for future research on plant–insect interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Um mutualismo dos mais notórios da região tropical é a interação entre formigas do gênero Azteca e árvores pioneiras do gênero Cecropia (Janzen, 1973;Beattie, 1985;Davidson, 1993;Longino, 2001;Heil & Mckey, 2003). Apesar de ser um sistema ecológico amplamente conhecido, não existem estudos que testem os efeitos do alagamento sobre a interação Azteca-Cecropia (mas veja : Emer, Venticinque & Fonseca, 2013;Câmara et al, 2018;Souza et al, 2020; para efeitos sobre outras espécies de formigas). Nessa associação a planta oferece alimento e local de nidificação (Janzen, 1969;Rickson, 1976) em troca de proteção contra herbívoros, parasitas, e até mesmo fertilização, fornecidas pelas formigas (Marting, 2018a).…”
Section: Introductionunclassified